Клинико-анатомические особенности иннервации почечных артерий у больных артериальной гипертензией = Clinical and anatomical features of innervation of the renal arteries in patients with arterial hypertension - Garmazi, Saber; Litvinenko, Marianna (Journal of Education, Health and Sport, 2016)
Garmazi S., Litvinenko M. A. Клинико-анатомические особенности иннервации почечных артерий у больных артериальной гипертензией = Clinical and anatomical features of innervation of the renal arteries in patients with arterial hypertension. Journal of Education, Health and Sport. 2016;6(2):293-300. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46810 http://ojs.ukw.edu.pl/index.php/johs/article/view/3406 https://pbn.nauka.gov.pl/works/717684 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016. Клинико-анатомические особенности иннервации почечных артерий у больных артериальной гипертензией Clinical and anatomical features of innervation of the renal arteries in patients with arterial hypertension Гармази С., Литвиненко М. А. Garmazi S., Litvinenko M. A. Одесский национальный медицинский университет, г. Одесса, Украина Odessa National Medical University, Odessa, Ukraine Summary Clinical and anatomical features of innervation of the renal arteries in patients with arterial hypertension Garmazi S., Litvinenko M.A. Odessa National Medical University, Odessa, Ukraine The aim of this study was the clinical and anatomical features of innervation of the renal arteries. The retrospective analysis of health statistics on the prevalence of resistant hypertension based on the Odessa Regional Mortem Bureau during 2011-2012 was conducted. The analysis of the results of the autopsy and subsequent histological examination of 30 bodies of deceased patients with resistant hypertension II and III stages has been done. The morphometry of renal arteries and their segments was conducted. Fragments of the renal artery were not larger than 1,0x1,0x1,0 cm, fixed in 10% neutral formalin and alcohol after standard wiring block embedded in paraffin. Sections 5.0-8.0 microns (in an amount of at least two sections with each block) were stained by the observation procedures recommended modern guidelines: hematoxylin and eosin, by Van Gieson; by Nissle, by Golgi and by Masson. The evaluation of the histological response rate in the vessels was performed visually and compared to the control group. The greatest density of accumulation in the nerve ganglia determined adventitia proximal renal arteries, preferably on the frontal surface. Ganglions sizes ranging from 80 to 220 microns, larger than when the ganglia are located in the proximal renal artery. The main part of the sympathetic ganglia, located at a depth of 2-3 mm. Postbifurcation ganglia localization occurs in 32.2% of cases. The degree of fibrosis of the renal artery wall in hypertension does not preclude the implementation of radiofrequency catheter sympathectomy. Key words: arterial hypertension, renal arteries, innervation, pathomorphology.